LOGICAL AND METHODOLOGICAL MEASUREMENTS OF THE IDEAL’S NATURE - Шоріна, Т. Г. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article on the materialist philosophy's basis reveals the ideal's dialectics, the logical and methodological problems in studying of this phenomenon.